Statistická analýza firemních nákladů - Jobbová, Katarína; Moll, Ivo, 1951-; Masarykova univerzita. Přírodovědecká fakulta (2006)
Diplomová práca spočíva v spolupráci s firmou Kinex, a.s., Bytča. Firma sa snaží implementovať do svojho podnikania princípy Lean Manažmentu a metódu Six Sigma. Ich popis je obsahom časti tejto práce. Jadro práce tvorí analýza konkrétnych nákladových položiek firmy Kinex, a.s., Bytča.
Master thesis arose from cooperation with a firm Kinex, a.s. Bytča. The firm tries to include princips of Lean Management and Six Sigma method into its management. Description of this methods is one part of the text. The main part is an analysis of concrete costs in Kinex, a.s. Bytča.
Vedoucí práce: Ivo Moll.
Diplomová práce (Mgr.)--Masarykova univerzita, Přírodovědecká fakulta, 2006.
Keywords: regresní analýza; statistická analýza; regression analysis; statistical analysis; diplomové práce; master's theses